Validation of the Pain Beliefs and Perceptions Inventory - Samuel F Mikail; Joyce L D'Eon; Théo A De Gagné (Pain Research and Management)
OBJECTIVE: To examine the test-retest reliability, construct validity and factor structure of the Pain Beliefs and Perceptions Inventory (PBPI).